Physiological, cognitive and neuromuscular effects of heat exposure on firefighters after a live training scenario. Issue 1 (2nd January 2021) - Abrard, Stanislas; Bertrand, Mathieu; De Valence, Timothée; Schaupp, Thierry
Abstract : This study investigated physiological, cognitive and neuromuscular performances in firefighters after a structural live-fire scenario. Changes in vital signs, environmental parameters and cognitive and neuromuscular performance were measured before and after a live-fire training session in a closed environment, in conditions similar to those one could encounter in a structural fire. Very high ambient temperature peaks were reached during the 30-min sessions. After the session, the forehead temperature was increased by 0.5 °C, mean water body loss was 639 ml and the mean heart rate increase was 7.5 bpm. Mental calculation speed did not vary significantly, however we observed a reduction in reaction time. These findings demonstrated that after 30 min of exposure, heat stress had little impact on firemen. Stress activation seems beneficial after firefighting operations. Normal vital parameters should allow re-engagement for a second firefighting task. This result must be compared with longer exposures.